ON THE HAUSDORFF MEASURE OF CERTAIN PLANE SET PROJECTIONS - Morales Rojas, Carlos Arnoldo (1999)
A characterization of plane sets whose projection have zero Hausdorff measure is given. This is obtained through the study of an angular density introduced first by Marstrand [2].